4-Amino-5-(arylaminomethyl)-2-(methylthio)furo[2,3-d]pyrimidines via Mitsunobu Reaction of 4-Amino-5-(hydroxymethyl)-2-(methylthio)furo[2,3-d]pyrimidine with N-Mesyl- and N-Nosylarylamines - Masevicius, Viktoras; Petraityte, Grazina; Tumkevicius, Sigitas (Synthesis, 2012)
An efficient method for the synthesis of 4-amino-5-(arylaminomethyl)-2-(methylthio)furo[2,3-d]pyrimidines via the Mitsunobu reaction of 4-amino-5-(hydroxymethyl)-2-(methylthio)furo[2,3-d]pyrimidine with N-mesyl- and N-nosylarylamines, and subsequent removal of the mesyl and nosyl groups, has been developed. The influence of substituents in the arylamine moiety on the Mitsunobu reaction was investigated. An unexpected nucleophilic substitution of a nitro group in the reaction of N-({4-amino-2-(methylsulfonyl)furo[2,3-d]pyrimidin-5-yl}methyl)-4-nitro-N-phenylbenzenesulfonamide with sodium methoxide was observed.
Keywords: alkylation; sulfonamides; heterocycles; oxidation; nucleophilic aromatic substitution